The principle of tax capacity in Peru A systematic review - Alexander Joao Peñaloza Mamani,; Shirley Fiorella Pastor Salazar,; Jorge Luis Monje Téllez,; Christian David Corrales Otazú, (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study presents a review of scientific articles from the last five years on the importance of the principle of tax capacity. The articles were sourced from a variety of academic search engines and include those from Peru and other countries where there is also interest in this topic. The following question was posed: How is the importance of the principle of tax capacity demonstrated? The objective of this research is to conduct a systematic review of the literature on the principle of tax capacity. Accordingly, the data from the scientific network has been utilized, encompassing all the documents reviewed from indexed academic journals, both nationally and internationally. This approach enables the recovery of diverse perspectives on this issue, encompassing varying points of view, methodologies, challenges, solutions, and recommendations. The reviewed studies demonstrate that this principle not only ensures a more equitable distribution of tax burden but also enhances the legitimacy of the tax system and fosters sustainable economic development. In this regard, the research indicates a need for further investigation into more precise methodologies for determining tax capacity and for the design of public policies that encourage voluntary compliance with tax obligations.